Evaluasi Mesin Furnace Chikka Menggunakan Metode Failure Mode Analysis (Fmea) Pt. Xx : Evaluation Of Chikka Furnace Machine Using Failure Mode Analysis (Fmea) Method Pt. Xx - Yuda Purwalaksana; Kardiman; Deni Hidayat; Stefanus Aldy Kurniawan; Rio Julianto Sukarman (Jurnal Pendidikan Teknik Mesin Undiksha, 2025)
The Furnace Chikka machine at PT. Xx plays a crucial role in the company’s production and operations. As one of the main tools used in material processing, this machine must function optimally to maintain production flow. However, over time, various potential failures can occur in the furnace system, which can affect its performance and efficiency. Therefore, an analysis is conducted to identify the risks that may arise and propose appropriate solutions. The method used in this study is Failure Mode and Effect Analysis (FMEA), aimed at identifying potential failure modes in the furnace machine, assessing their impact, and calculating the level of risk that could arise. Data collection is carried out through field observations, discussions with technicians, and literature review. The risk assessment utilizes three main parameters: Severity, Occurrence, and Detection, which are calculated to determine the Risk Priority Number (RPN). The results of this study provide recommendations for maintenance and early detection to minimize further damage.